Power Analog of Trigger Schmitt’s - S. Martirosyan; J. Torikyan
Our designed electrical appliance is intended for use in managing and controlling devices as a powerful electrical coupling hub. It is a functional equivalent of the HEF4093 integrated circuit and is assembled on the basis of a modern integrated circuit (comparator) and a MOSFET transistor for power output. The input of the scheme requires digital or analog signal. At the output of the device it is possible to switch the load, which may have high currents. The transistor is protected from the short load mode. The structure of scheme allows the free choice of comparator and transistor based on the required electrical parameters. The device model has been tested on 0.5-2 amperes range.
Keywords: Physics; Instruments, apparatus, components common to several branches of physics; Electronic and magnetic devices; microelectronics